ОРГАНІЗАЦІЙНО-ЗМІСТОВІ АСПЕКТИ АКАДЕМІЧНОЇ МОБІЛЬНОСТІ СТУДЕНТІВ У США - Khomynets , Svitlana; Kanyuk , Oleksandra (Науковий вісник Ужгородського університету. Серія: «Педагогіка. Соціальна робота», 2025)
Інтеграційні процеси, які відбуваються в сучасному суспільстві не оминули й систему вищої освіти. Формується єдиний світовий освітній простір, що виражається, насамперед у координації освітніх стандартів, програм, підходів до підготовки майбутніх фахівців у закладах вищої освіти різних країн. Інтеграція системи вітчизняної вищої освіти у світовий освітній простір є фактором її інтернаціоналізації та зумовлює зростання академічної мобільності студентів, значний досвід реалізації якої має вища школа США. Метою статті є дослідження організаційно-змістових аспектів академічної мобільності студентів у вищій школі США. Методи дослідження: аналіз і синтез психолого-педагогічної літератури, вивчення досвіду діяльності провідних американських університетів у контексті академічної мобільності, систематизація, узагальнення. Встановлено, що основними цілями академічної мобільності студентів у США є оволодіння здобувачами професійною та міжкультурною компетенціями, придбання культурного досвіду країни перебування через навчання за програмами академічної мобільності, підготовку у літніх і вечірніх мовних школах, виконання проекту, дослідження. The integration processes, taking place in modern society, impact the system of higher education. The united world educational environment is being formed, demonstrating the coordination of educational standards, programmes, approaches to the training of future specialists in higher educational institutions of various countries. The integration of the system of Ukrainian higher education into the world educational environment determines the growth of academic mobility of students, for which the USA higher education is famous about. The aim of the article is to study the organizational and aontent aspects of academic mobility of students in the USA higher education. Research methods applied: analysis and synthesis of psychological and pedagogical literature; study of experience of particular American universities in the context of academic mobility, systematization, and generalization. Internationalization has been defined as one of the most important principles of academic mobility organization in the USA. Internationalization is a process in which the goals, functions and organization of educational services acquire an international dimension. This process involves the integration of national education systems, defining and development of general and universal concepts and components of their functioning, i.e. those principles that form the basis of diversity of national cultures, contribute to their mutual enrichment and provide systemic changes in higher education. Academic mobility is a form of organization of the educational process (in particular, by distance learning means), which provides the opportunity to study, teach, train or carry out research in another educational institution, even abroad, resulting in self-realization in learning and professional activities. The temporary study in other institutions of higher education is a characteristic feature of academic mobility of students. The main goals of academic mobility of students in the USA are the acquisition of professional and intercultural competencies, cultural experience of the host country through training in academic mobility programmes, in summer and evening language schools, project implementation, and research.